Predicting streamflow distributions and flow duration curves from landscape and climate. (September 2015) - Doulatyari, Behnam; Betterle, Andrea; Basso, Stefano; Biswal, Basudev; Schirmer, Mario; Botter, Gianluca
Highlights: Estimating pdfs of river flows based on limited climatic and landscape features. Flow statistics are well reproduced in 11 test catchments. Implications for flow regime characterization in sparsely gauged catchments. Abstract: Characterizing the probability distribution of streamflows in catchments lacking in discharge measurements represents an attractive prospect with consequences for practical and scientific applications, in particular water resources management. In this paper, a physically-based analytic model of streamflow dynamics is combined with a set of water balance models and a geomorphological recession flow model in order to estimate streamflow probability distributions based on catchment-scale climatic and morphologic features. The models used are described and the novel parameterization approach is elaborated on. Starting from rainfall data, potential evapotranspiration and digital terrain maps, the method proved capable of capturing the statistics of observed streamflows reasonably well in 11 test catchments distributed throughout the United States, east of the rocky mountains. The method developed offers a unique approach for estimating probability distribution of streamflows where only climatic and geomorphologic features are known.